2010
DOI: 10.3382/ps.2009-00571
|View full text |Cite
|
Sign up to set email alerts
|

Selenium enrichment of table eggs

Abstract: Selenium is an essential trace element with a recommended dietary allowance for human adults of 55 μg/d. However, there is evidence that greater dietary intakes may have possible health benefits, including a reduction in the risk of cancer. Several studies have shown the feasibility of enriching eggs using organic Se and that Se-enriched eggs are an effective way to supplement human diets. However, few studies have examined the response of egg Se concentration to high (>1 μg/g) dietary organic Se intake by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 18 publications
5
19
1
Order By: Relevance
“…The laying performances observed in the present study are in contrast with the results reported by Bennett and Cheng (2010); these Authors did not observe any effect of the Se diet content on hens egg production, despite the lowest Se diet level used was 0.31 and the highest 5.43 mg/kg and the reason of that might be due to the reduced numerousness of the analysed samples. Also for laying hens Scheideler et al (2010) refer about an egg production increment only when the Se content rose from 0.5 to 0.75 mg/kg of diet; in this case, the selenium to vitamin E ratio was not kept constant and probably it caused a decrease of absorption of vitamin E and the observed reduction of a-tocopherol in the yolk.…”
Section: Discussioncontrasting
confidence: 57%
“…The laying performances observed in the present study are in contrast with the results reported by Bennett and Cheng (2010); these Authors did not observe any effect of the Se diet content on hens egg production, despite the lowest Se diet level used was 0.31 and the highest 5.43 mg/kg and the reason of that might be due to the reduced numerousness of the analysed samples. Also for laying hens Scheideler et al (2010) refer about an egg production increment only when the Se content rose from 0.5 to 0.75 mg/kg of diet; in this case, the selenium to vitamin E ratio was not kept constant and probably it caused a decrease of absorption of vitamin E and the observed reduction of a-tocopherol in the yolk.…”
Section: Discussioncontrasting
confidence: 57%
“…Se-enriched eggs have remained to be a virtuous source of Se for humans (Surai et al 2007). Bennett and Cheng (2010) demonstrated that Se supplementation is a practical way of producing Se-enriched eggs for the consumers. According to NRC (1994), selenium requirement for laying hens ranges from 0.05 to 0.08 ppm, however, AAFCO (2003) recommended 0.3 ppm maximum allowable level.…”
Section: Introductionmentioning
confidence: 99%
“…According to Pappas et al (2005) and Gajcevic et al (2009), selenium, supplemented in diets for laying birds, is able to keep good values of Haugh unit for commercial eggs when stored. In addition, selenium can be incorporated into eggs through dietary supplementation of egg-laying hens, especially when supplied in the organic form, which is more efficient than the inorganic form (Payne et al 2005;Utterback et al, 2005, Bennett & Cheng, 2010. Breeding birds fed diets supplemented with organic selenium provides eggs with increased concentration of that mineral (Osman et al, 2010).…”
Section: Introductionmentioning
confidence: 99%